The Effect of Government Support on the Purchase Intention of Electric Vehicles - Diah Wulandari; Albert Sugianto; Rani Rahputri; Julbintor Kembaren; Iman Permana (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the influence of psychological factors and government support on consumers' purchase intention toward electric vehicles (EVs) in the Greater Jakarta (Jabodetabek) area by employing an extended Theory of Planned Behavior (TPB) framework. The model investigates the effects of emotional value, attitude toward EVs, subjective norm, perceived behavioral control (PBC), and the moderating role of government support. A quantitative survey method was applied to 291 potential EV consumers aged 18 years and above residing in Jabodetabek. Data were collected through an online Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that emotional value has a significant positive effect on attitude toward EVs, and both attitude and subjective norm significantly enhance purchase intention. Attitude is also found to significantly mediate the relationship between emotional value and purchase intention. Conversely, PBC does not exhibit a significant effect on purchase intention. Moreover, government support does not moderate the relationships between attitude or subjective norm and purchase intention and only shows a weak, negative moderating effect on the relationship between PBC and purchase intention. Overall, the results suggest that EV purchase intention in Jabodetabek is driven more strongly by emotional and normative factors than by perceived behavioral control or perceived government support.